2019
DOI: 10.1111/ecog.04722
|View full text |Cite
|
Sign up to set email alerts
|

Millennial‐scale change in the structure of a Caribbean reef ecosystem and the role of human and natural disturbance

Abstract: Caribbean coral reefs have transformed into algal-dominated habitats over the past half-century, but the role of specific anthropogenic drivers is unresolved due to the lack of ecosystem-level data predating human disturbance. To better understand the extent and causes of long-term Caribbean reef declines, we produced a continuous 3000-yr record of the ecosystem state of three reefs in Bocas del Toro, Caribbean Panama. From fossils and sediments obtained from reef matrix cores, we tracked changes in reef accre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…from ~1800 to 1000 yrs BP. Accretion rates in sites sampled in this and previous studies (Cramer et al 2017(Cramer et al , 2020. Recent samples with important trends are indicated by the black rectangle.…”
Section: Natural Versus Anthropogenic Drivers Of Reef Cessationmentioning
confidence: 83%
See 1 more Smart Citation
“…from ~1800 to 1000 yrs BP. Accretion rates in sites sampled in this and previous studies (Cramer et al 2017(Cramer et al , 2020. Recent samples with important trends are indicated by the black rectangle.…”
Section: Natural Versus Anthropogenic Drivers Of Reef Cessationmentioning
confidence: 83%
“…Notwithstanding, one of these studies (Cramer et al 2020) reported an increase in the proportion of infaunal deposit-and suspension-feeding bivalve communities over the last 1000 years and suggested this may be evidence for a gradual decrease in oxygen levels within the reef sediments over time.…”
Section: Introductionmentioning
confidence: 99%
“…However, based on observations in the area of phase shifts to algae and increased land clearing activities, it is likely to be linked to land‐based runoff and algal overgrowth. Observed elevated sea surface temperatures, increased nutrients, and overexploitation of herbivorous reef fishes in the area could all promote algal growth (Cramer et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of seawater and macroalgae nitrogen content since the 1990s from the Florida Keys implicates land-based nutrients from agriculture and development in the decades-long coral declines within that reef tract [57]. Studies based on historical and paleontological data also suggest that early reef ecosystem declines in Barbados and Panama may be attributed to increases in coastal runoff from historical land clearing for agriculture [17,[58][59].…”
Section: The Role Of Local and Global Human Stressorsmentioning
confidence: 99%